2004
DOI: 10.1126/science.1095733
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in Algal Endosymbioses Shapes Growth in Reef Corals

Abstract: The relation between corals and their algal endosymbionts has been a key to the success of scleractinian (stony) corals as modern reef-builders, but little is known about early stages in the establishment of the symbiosis. Here, we show that initial uptake of zooxanthellae by juvenile corals during natural infection is nonspecific (a potentially adaptive trait); the association is flexible and characterized by a change in (dominant) zooxanthella strains over time; and growth rates of experimentally infected co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
534
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(584 citation statements)
references
References 17 publications
26
534
5
Order By: Relevance
“…However, clade D may not be the perfect symbiotic partner all the time. In juvenile coral stages, corals infected with clade D grew slower than those with clade C (Little et al, 2004), suggesting that members of clade C may provide other growth benefits than clade D algae despite their greater temperature sensitivity (Rowen, 2004). It should also be noted that not all subgroups of clade D confer temperature tolerance in corals (Abrego et al, 2008).…”
Section: The Fluctuation Of the Symbiotic Algal Compositionmentioning
confidence: 99%
“…However, clade D may not be the perfect symbiotic partner all the time. In juvenile coral stages, corals infected with clade D grew slower than those with clade C (Little et al, 2004), suggesting that members of clade C may provide other growth benefits than clade D algae despite their greater temperature sensitivity (Rowen, 2004). It should also be noted that not all subgroups of clade D confer temperature tolerance in corals (Abrego et al, 2008).…”
Section: The Fluctuation Of the Symbiotic Algal Compositionmentioning
confidence: 99%
“…Hosting these symbionts, however, likely represents a trade-off in terms of growth rate and/or reduced carbon uptake in juveniles (Little et al 2004, Cantin et al 2009 Higher abundance of D1a may have resulted from (1) changes in symbiont communities as a result of severe physiological stress resulting in bleaching (e.g. Baker et al 2004, Jones et al 2008), (2) differential survival and/or reproduction (e.g.…”
Section: Biogeographic and Environmental Patterns Inmentioning
confidence: 99%
“…Partner-switching following a bleaching event may occur by recovery with different symbionts that are better suited to the prevailing conditions [4,11], an idea termed the Adaptive Bleaching Hypothesis (ABH; 'adaptive' referring to a beneficial trait that can be positively selected for; [12]). In particular, recovery with heat-tolerant symbionts can increase resistance to future thermal bleaching [8], but at a potential energetic cost [13][14][15][16]. Investigations of the ABH have revealed that, although corals sometimes change their symbionts [8,9,[17][18][19][20][21], this does not always occur: sometimes corals recover with the same symbiont community they had prior to stress [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Because symbiont types differ not only in heat tolerance, but also in photosynthetic performance [14,30], energetics [31] and associated coral growth rates [13,15], overall symbiosis function should be determined by the contributions of all symbionts [32]. However, the functional consequences of variation in symbiont community composition are poorly understood, in part because molecular methods to quantify mixed assemblages have only recently been developed [33,34].…”
Section: Introductionmentioning
confidence: 99%